Effectiveness Of Peatland Restoration Implementation In Riau Province - Febri Yuliani (Iapa Proceedings Conference, 2018)
The peat phenomenon that occurs in Riau Province negatively impacts the environmental conditions resulting from the management and utilization of peat ecosystem areas that are out of control and irresponsible. For example, forest fires and land that occurred have an impact of smoke haze that hit Riau and Sumatra region. This study aims to analyze the Effectiveness of Peat Restoration in Riau Province. This research is done by using qualitative method. The peatland restoration program that has been established in several districts in Riau Province is also influenced by several factors that influence the implementation process, including the following: (1) Conceptualization of Peatland Restoration Program. Since the restoration program has been rolled out, there are still many parties who do not understand what peatland restoration is. This caused inequality in the implementation of the restoration program. So far, the community considers restoration of peatlands to the extent of government tasks, and for local governments the restoration program is only a pilot project of the central government. In fact, it is wrong, therefore the conceptualization of this restoration must be clear and submitted continuously to the government apparatus, stakeholders and the community. (2) Implementing Institutional Preparedness The readiness of the implementing agency in this case is whether the institutions involved in this peat land restoration program are ready to implement with all the preparations in the form of activity designs, socialization to be performed, supporting funding, and how to respond to society. (3) The Encouragement of Good Local and Formal Figures at Provincial, District, District and Village Levels. In implementing peatland restoration programs, encouragement or support of parties other than those of the relevant official are indispensable, both formal and informal. The conclusions of this study indicate that overall government efforts to implement peat restoration have not been too effective. Some districts have successfully restored their peatlands but in some districts peat restoration has not been an important agenda in the formulation and implementation of policies in the district